American Legal Education: The Catholic Solution - Czarnetzky, John M. (Chrześcijaństwo-Świat-Polityka, 2025)
The article examines structural deficiencies in American legal education, emphasizing the neglect of foundational inquiry into the nature and purpose of law. The author argues that the dominance of legal positivism and the abandonment of natural law traditions result in insufficient intellectual and ethical formation of future lawyers. This technocratic approach to legal training contributes to professional identity crises. The proposed solution is the reintroduction of Catholic legal philosophy—particularly the Thomistic concept of the common good—as a framework for understanding law more comprehensively. The case of Ave Maria School of Law illustrates the practical applicability of this educational model.